Impact of fasting blood glucose on prognosis after acute large vessel occlusion reperfusion: results from a multicenter analysis - Luo, Bin; Xiang, Yi; Meng, Fanlei; Wang, Yubo; Zhang, Zhenzhong; Ren, Hecheng; Ma, Lin (Frontiers in Neurology, 2024)
Objective To analyze the effect of fasting blood glucose levels after reperfusion of acute large vessel occlusion (ALVO) on patient functional prognosis. Methods Retrospectively included ALVO patients from three large stroke centers in China, all of whom achieved vascular reperfusion after mechanical thrombectomy or bridging thrombolysis. The prognosis scores of all patients at 90 ± 7 days post-recanalization were categorized into a good prognosis group (mRS 0–2) and a poor prognosis group (mRS 3–6). The relationship between mean blood glucose levels at 72 h post-recanalization and prognosis was explored using multivariable logistic regression analysis. Then we measured the area under the ROC curve for all factors to assess their predictive performance. Results (1) Totally 2,056 patients were included in the study, with 1,488 males and 568 females. There were 1,370 patients in the good prognosis group (mRS 0–2) and 686 in the poor prognosis group (mRS 3–6). (2) The two groups exhibited significant differences in terms of age, preoperative mRS score, history of diabetes, and mean fasting blood glucose (MFBG) (p < 0.001). (3) With 90-day mRS as the outcome variable, all independent variables were included in Univariate and multivariate regression analyses analysis, and the results showed that: age, preoperative mRS score, history of diabetes, and MFBG are all independent predictors of prognosis after recanalization of ALVO, with MFBG demonstrating a higher predictive power than the other factors (AUC = 0.644). Conclusion Various factors are correlated with the prognosis in patients who have undergone ALVO recanalization. Notably, the MFBG level demonstrates a significant predictive value for outcomes within the first 72 h following the recanalization procedure.